Amniotic membrane as an option for treatment of acute Achilles tendon injury in rats - Nicodemo,Mariana de Castro (2017)
Abstract Purpose: To evaluate the effect of human amniotic membrane (hAM) fragment on inflammatory response, proliferation of fibroblast and organization of collagen fibers in injured tendon. Methods: Sixty rats were divided into 3 groups: C - surgical procedures without tendon lesion and with simulation of hAM application; I - surgical procedures, tendon injury and simulation of hAM application; T - surgical procedures, tendon injury and hAM application. These groups were subdivided into four experimental times (3, 7, 14 and 28 days). The samples underwent histological analysis and ATR-FTIR spectroscopy. Results: Histological analysis at 14 days, the T group showed collagen fibers with better alignment. At 28 days, the I group presented the characteristics described for the T group at 14 days, while this group presented aspects of a mature connective tissue. FT-IR analysis showed a clear distinction among the three groups at all experimental times and groups T and I presented more similarities to each other than to group C. Conclusion: Acute injury of tendon treated with human amniotic membrane fragment showed a faster healing process, reduction in inflammatory response, intense proliferation of fibroblasts and organization of collagen fibers.